THE INFLUENCE OF THE IMPLEMENTATION OF REGIONAL INNOVATION POLICY ON THE EMPOWERMENT OF THE CREATIVE ECONOMY IN THE TRADITIONAL MALAY FOOD CULINARY SECTOR IN PEKANBARU CITY - Achmad Fauzi; Seno Andri; Muchid Albintani; Febri Yuliani (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The creative economy of the traditional Malay food culinary sector has strategic potential in improving the regional economy and preserving local culture in Pekanbaru City. However, the challenges in developing this sector require the support of targeted innovation policies. This study aims to analyze the effect of the implementation of regional innovation policies on the empowerment of the creative economy of the traditional Malay food culinary sector in Pekanbaru City. The research method uses a quantitative approach with an explanatory research design. The population of the study was traditional Malay food culinary entrepreneurs in Pekanbaru City, with a sample of 150 respondents selected using purposive sampling techniques. Data collection was carried out through structured questionnaires and in-depth interviews. Data analysis used Structural Equation Modeling (SEM) with the help of SmartPLS software. Independent variables include MSME development policies, marketing digitalization programs, production technology assistance, training and certification, and access to microfinance. Dependent variables include increased business turnover, market expansion, product innovation, labor absorption, and business sustainability. The results of the study indicate that the implementation of regional innovation policies has a positive and significant effect on the empowerment of the creative economy of the traditional Malay culinary sector. The marketing digitalization program has the most dominant influence, followed by microfinance access policies and production technology assistance. This research provides a theoretical contribution in the form of a creative economic empowerment model based on local wisdom and practically produces policy recommendations for optimizing regional innovation programs in developing the traditional culinary sector.